Application of Exploratory Modeling in Support of Transdisciplinary Inquiry: Regulation of Fishing Bycatch of Loggerhead Sea Turtles in Gulf of Ulloa, Mexico - Bojórquez-Tapia, Luis A.; Ponce-Díaz, Germán; Pedroza-Páez, Daniela; Díaz-de-León, Antonio J.; Arreguín-Sánchez, Francisco (Frontiers in Marine Science, 2021)
The fishing bycatch of the loggerhead sea turtle (Caretta caretta) epitomizes the challenges of designing fisheries management strategies to protect highly migratory, endangered species. We present here the case of turtle bycatch in the Gulf of Ulloa, Mexico, in which conservation advocacy groups requested the United States Government to apply the legal provisions for preventing fishing bycatch of protected living marine resources (PLMR). Because these provisions implied the possibility of trade sanctions, the Mexican government had to devise policies equivalent to those imposed on the United States’ fleet. While conservation advocacy groups claimed that the effect of fishing bycatch was proven, the federal fisheries agency disregarded the facts for political reasons. Evidently, there was a need for a practical approach to address this highly contested policy-making problem characterized by limited data, deep uncertainties, and urgency for results. Our goal here is to present the implementation of an exploratory modeling rationale to tackle this sort of complex socio-ecological technological problem. We focused on identifying the bycatch level at which the environmental authorities would be compelled by law to act in protecting the loggerheads. We combined ecological risk analysis and area-oriented multiple-use framework to evaluate a wide range of plausible scenarios consistent with the available data. Results identified the bycatch level that indicated a potential critical transition to a low resilience state of the loggerhead population, and the proper multiple-use management scheme. Our findings were used to formulate regulations aimed to set a bycatch cap and a refuge area for the loggerhead population in the region.